The pace of MNEs' sequential entries: Cumulative entry experience and the dynamic process - Gao, Gerald Yong; Pan, Yigang (Journal of international business studies, 2010)
This study examines the pace with which multinational enterprises undertake sequential entries in a foreign market. We focus on learning effects from cumulative entry experience of different modes within a host market. Moreover, we investigate the dynamic process of entry mode switch, and how cumulative entry experience reduces the expansion constraint. Using a dataset of sequential entries by US firms in China during 1979-2002, we find that the impact of cumulative entry experience on the pace of sequential entries varies across different modes. Further, firms with more cumulative entry experience can cope with the constraint of entry mode switch.